The asylum‐process, bicultural identity and depression among unaccompanied young refugees. (8th October 2020) - Oppedal, Brit; Ramberg, Visnja; Røysamb, Espen
ABSTRACT: Introduction: The overall aim of the present study was to expand our knowledge about depression among unaccompanied refugee minors in the years after they were granted protection in Norway. Predictors were contextual variables in terms of the asylum‐process, acculturation variables in terms of bicultural identity, and demographic information such as residence‐time. Method: Register data and cross‐sectional self‐report questionnaire data were collected from 895 unaccompanied young refugees (UYRs). They originated in 31 different countries, the majority was from Afghanistan, 82.4% were boys, and average residence‐time was 2.5 years. Results: The length of the asylum‐process was not associated with depression while heritage identity and residence‐time were. Moderating analyses showed that an over‐time steady decrease in depression was present for UYRs with a strong heritage identity. The prevalence of depression symptoms dropped from an initial 40%–14% among youth with 10 years of residence. Majority identity had neither direct nor indirect effects on depression. Conclusion: To optimize the psychosocial support offered to unaccompanied refugee minors during transition to stable resettlement, we need more substantial information about the aspects of the asylum‐seeking process that increase the risk for mental health problems among them. In the years following resettlement, a strong heritage, but not majority identity was associated with lower levels of depressive symptoms. The findings are discussed in relation to structural barriers to bicultural identity formation and integration embedded in the way psychosocial support and education for these youths are structured, and implication for future research.